PERILAKU PENGGUNAAN MEDIA SOSIAL SEBAGAI SUMBER BERITA OLEH GENERASI Z (STUDI PADA MAHASISWA DI JAKARTA SELATAN) - Sevilla, Vinta; Saputra, Windhi T; Samodro, Dewanto (Departemen Ilmu Komunikasi Universitas Andalas, 2024)
The existence of hoaxes is now emerging on a massive scale and is difficult to define, so that media literacy skills are now the main requirement to avoid hoax information. Searching for and getting information is now very easy, and even without realizing it, information appears without the public having to look for it. The waves and flow of information are now very strong and literacy skills are needed. The need for media literacy is important because information in society comes in various contexts, including political information to health information. Generation Z is a part of society who is currently in a productive period, and uses information as their main source in living their lives. This research aims to see how Generation Z, in this case students, uses social media to search for news information. This research uses Wilson's Information Search Model, by looking at how Generation Z searches, finds and evaluates the information they get. The method used is descriptive qualitative with the aim of describing and viewing the conditions and situations of phenomena and realities that occur in Generation Z in utilizing social media as a means of information to obtain news. This research shows the results that Generation Z prefers to search for news using social media because social media has the advantage of speed and is equipped with easy features, and shows the information needed. Testing the credibility of information sourced from social media, Generation Z usually carries out further searches on search engines.